IMPLEMENTASI PEMBELAJARAN IPA TERPADU KELAS V DI MI AL-MADINA PRAMBANAN - Andi Setiyawan; M. Rofi Fauzi (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2022)
Integrated science learning at the elementary school level is essentially bringing students into more real conditions, not just theoretical. Integrated science learning at the basic level aims to foster scientific attitudes and mindsets in students, so that later students are expected to be able to solve various problems they encounter in everyday life with a logical and systematic scientific mindset. This research is a classroom action research conducted to find out how the implementation of integrated science learning in class V at MI Al-Madina Prambanan and to know the urgency of the learning implementation process and also the problems and solutions in the integrated science learning process at MI Al-Madina Prambanan. The integrated science learning for class V at MI Al-Madina Prambanan is carried out referring to the basic concept of integrated science learning which brings students to real learning with the hope that students will grow scientific attitudes and mindsets which can later become provisions for students in solving various problems that arise. dealt with logically and systematically.